2019
DOI: 10.15406/jdvar.2019.08.00241
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of clinical, biometric, cosmetic and microscopic outcomes of four suture techniques for cutaneous closure of laparotomy wounds: an experimental study in rabbits

Abstract: The purpose of this study is to identify a suture technique that provides superior cosmetic outcomes and proper wound healing for skin closure after midline laparotomy of small animals in a rabbit model. This study also attempts to clarify the role of selected four suture patterns in wound healing, wound complications, cosmetic impacts and histopathology on the laparotomy skin wound. Twenty four female rabbits of white New Zealand and California breeds were used for this experimental study. Four suture pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Very recently, Thangavelu et al (2022) showed that the leaf methanolic extracts of P. crispum , whose synonym is P. sativum , exhibited potent wound healing and anti-inflammatory activities on the human lung cancer cell lines by enhancing cell migration [ 15 ]. Interestingly, in another study, parsley was used as a maintenance diet for cutaneous closure of wounds in rabbits as a postoperative care after the surgery [ 16 ]. Elsewhere, P. crispum was also investigated for immunomodulatory and wound healing activities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Thangavelu et al (2022) showed that the leaf methanolic extracts of P. crispum , whose synonym is P. sativum , exhibited potent wound healing and anti-inflammatory activities on the human lung cancer cell lines by enhancing cell migration [ 15 ]. Interestingly, in another study, parsley was used as a maintenance diet for cutaneous closure of wounds in rabbits as a postoperative care after the surgery [ 16 ]. Elsewhere, P. crispum was also investigated for immunomodulatory and wound healing activities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%